Edukasi Kesehatan tentang Pola Hidup Sehat dan Pemeriksaan Payudara Sendiri: Health Education on Healthy Lifestyles and Breast-Self Examinations - Cathryne, Joice; Houghty, Grace Solely; Mambu, Ian Ruddy; Kasenda, Edson (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2024)
Breast cancer is the number one cause of death for women. Many women realize they have breast cancer after being in the final stage, as experienced by two church members who are currently undergoing breast cancer treatment. The interview results revealed that some church members had a family history of breast cancer, underscoring the importance of implementing prevention education and breast self-examination within the church. One of the causes of breast cancer is an unhealthy lifestyle, a lack of awareness, a lack of information, and the feeling that they are fine. No family history of the disease makes women too lazy to do breast self-exam. This activity was carried out in March 2024 with the target of women aged 15-55 years totaling 33 people. This activity is in the form of providing education on healthy lifestyles and how to prevent them by doing breast self-exam. At the beginning and end of the activity, participants were given a pretest and posttest to measure their level of knowledge, then continued with a demonstration and redemonstration of breast self-exam practice. The results of the pretest were 66.1% and the posttest was 79.5%, where there was an increase in knowledge about healthy lifestyles and breast self-exam. This increase is expected to be followed by the routine implementation of breast self-exam practices every month, correctly and appropriately, so that the mortality rate of women due to breast cancer can decrease.